Sensing a Lagoon: Distance, Care and Cormorants - Quagliati, Noemi (Lagoonscapes)
By questioning the dichotomy between epistemology ‘from above’ and ‘from below’, this article presents a multidimensional and multisensory analysis of the Venetian Lagoon ecosystem. It first investigates remote sensing techniques applied to Venetian coastal management, artisanal fishery, and archaeology, tracing the evolution of environmental remote sensing through the work of geographer Evelyn L. Pruitt, who coined the term. The focus then shifts to the cormorants inhabiting the lagoon, whose movement between air and water in search of food – sparking conflicts with fish farmers and anglers – reframes the divide between the world above and the one below the water’s surface, offering a more-than-human perspective on the so-called vertical turn.